Road shallow wet and soft foundation backfill material and preparation method thereof
By using components such as construction waste, modified diatomaceous earth, cement, modified chitosan and sodium carbonate in backfills, the lack of structural strength and stability of backfills in shallow and soft foundations of roads is solved. Problem, achieving higher mechanical properties and durability.
Patent Information
- Application Number
- CN202411627767.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
The existing backfills are used in shallow wet and soft foundations on roads, with poor structural strength and stability, resulting in insufficient bearing capacity and durability.
Using backfill formulas including construction waste, modified diatomaceous earth, cement, modified chitosan and sodium carbonate, the porosity of backfills is improved by the porous structure of modified diatomaceous earth and the gelation effect of cement. Mechanical properties; modified chitosan enhances adhesion properties, sodium carbonate optimizes hydration reaction and structural compactness.
It significantly improves the structural strength, stability and crack resistance of the backfiller, enhances its compressive strength, tensile strength and toughness, and extends the service life of the road.
Smart Images

Figure BDA0005135160290000081 
Figure BDA0005135160290000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of backfill materials, and in particular to a backfill material for shallow wet soft foundation of a road and a preparation method thereof. Background Art
[0002] Shallow soft foundation of roads refers to a type of foundation encountered in road projects. The moisture content in the foundation soil is much higher than its optimal moisture content, resulting in a loose soil structure and large voids. Backfill is usually used for replacement to improve the bearing capacity and stability of the foundation and ensure the safety and durability of the road project.
[0003] Backfill materials usually include the following raw materials: sand, gravel, slag, construction waste, etc. Various raw materials are mixed. Construction waste and slag are used as backfill materials to reduce project costs. Sand and gravel can provide good permeability and stability, improve the overall project performance, and have good construction performance.
[0004] Construction waste is irregular in shape and size. Although mixing it with sand and soil can reduce the gaps in the backfill material, the adhesion between construction waste and sand and soil is low, which may lead to a decrease in the structural strength and stability of the backfill material. Summary of the invention
[0005] In order to improve the problem of poor structural strength and stability of backfill materials, the present application provides a backfill material for shallow wet and soft foundation of a road and a preparation method thereof.
[0006] The present application provides a road shallow soft foundation backfill material, which adopts the following technical solution: A backfill material for shallow wet soft foundation of a road comprises the following raw materials by weight: 40-50 parts of construction waste soil, 10-15 parts of modified diatomaceous earth, 15-20 parts of cement, 7-10 parts of modified chitosan, 60-70 parts of water and 5-9 parts of sodium carbonate.
[0007] By adopting the above technical solution, construction waste as backfill material not only realizes the resource utilization of waste, but also has a good microstructure, which is helpful for mixing with other components to form a dense mixture; modified diatomaceous earth has a porous structure, high specific surface area and adsorption, and can adhere to the surface and pores of construction waste, refine the pore structure of backfill material, reduce the internal coarse pores, increase the fine pores, increase the porosity of backfill material, and improve the antifreeze performance of backfill material. Cement, as a gelling material, can react with other components in the backfill material to form a stable consolidation body, improve the overall stability and bearing capacity of the backfill material, and improve the compressive strength, shear strength and other mechanical properties of the backfill material through the hydration of cement.
[0008] Modified diatomite has good volcanic ash properties and can also react with cement hydration products to form a denser structure and improve the compressive strength of the backfill. Modified chitosan has good biocompatibility and reinforcing properties. It can be filled between construction waste, modified diatomite and cement, so that the various components in the backfill are tightly bonded, the density of the backfill is improved, the compressive strength, tensile strength and toughness of the backfill are enhanced, cracking is reduced, and the crack resistance of the backfill is improved. Sodium carbonate can accelerate the hydration process of cement, shorten the setting time of the backfill, and optimize the microstructure of the backfill, reduce the internal coarse pores, increase the fine pores, and improve the density and durability of the backfill.
[0009] Preferably, the pretreatment of the construction waste comprises the following steps: crushing the construction waste, dispersing it in anhydrous ethanol, stirring, drying, heating it at 400-450°C for 30-35min, dispersing it in water, adding fly ash and silane coupling agent, stirring at 80-85°C for 1-2h, and drying to obtain the construction waste.
[0010] By adopting the above technical solution, the construction waste is crushed, washed with anhydrous ethanol to remove organic impurities in the construction waste, and further calcined to remove organic matter and moisture in the construction waste, thereby improving the stability and strength of the construction waste. The calcined construction waste has better mechanical properties such as compressive strength and wear resistance. Then fly ash and silane coupling agent are added. Fly ash, as fine aggregate, can fill the voids in the construction waste and improve the density of the material. At the same time, the volcanic ash activity of fly ash can subsequently react with cement hydration products to further enhance the mechanical properties of the material.
[0011] The addition of silane coupling agent can further optimize the dispersion of fly ash and construction waste, reduce agglomeration, and thus improve the compressive strength and tensile strength of the backfill material; silane coupling agent can also optimize the microstructure of the material, reduce the internal coarse pores, increase the fine pores, and improve the porosity and density of the backfill material. The use of fly ash can improve the corrosion resistance of concrete, reduce the corrosion of sulfate and chloride ions, and silane coupling agent can form a protective layer, reduce the penetration of moisture and harmful substances, and improve the durability of the material.
[0012] In addition, silane coupling agents can improve the interfacial bonding between fly ash and construction waste and organic or inorganic matrices. Through chemical bonding, silane coupling agents can enhance the adhesion between different materials and improve the overall performance of composite materials.
[0013] Preferably, the mass ratio of the construction waste, fly ash and silane coupling agent is 1:0.2-0.3:0.08-0.09.
[0014] By adopting the above technical solution, the mass ratio of construction waste soil, fly ash and silane coupling agent is further limited within a certain range, thereby improving the compactness, dispersion, compressive strength and tensile strength of construction waste soil. Fly ash has certain viscosity and mechanical properties, and can be loaded on the surface and pores of construction waste soil to improve the mechanical properties of construction waste soil. Silane coupling agent can form chemical bonds with fly ash and construction waste soil, enhance the interface bonding between fly ash and construction waste soil, and improve the overall performance of backfill materials, including its mechanical properties and durability.
[0015] Silane coupling agent can also improve the compressive strength, tensile strength and durability of backfill materials, thereby enhancing its overall mechanical properties. By optimizing the dispersion of slag particles and reducing agglomeration, silane coupling agent can improve the compressive strength and tensile strength of construction slag backfill materials and enhance their overall mechanical properties. The mixture of construction slag, fly ash and silane coupling agent has a synergistic effect, improving the mechanical strength of construction slag, and improving the crack resistance and durability of construction slag.
[0016] Preferably, the construction debris includes concrete blocks, bricks, and stones generated when old buildings are demolished.
[0017] By adopting the above technical solution, the construction debris generated when demolishing old buildings is used to realize the resource utilization of waste. In addition, the construction debris has a good microstructure. As backfill material, it has good compressive strength and stability in combination with other components, thereby reducing the demand for traditional filling materials and saving costs.
[0018] Preferably, the method for preparing the modified diatomite comprises the following steps: (1) calcining diatomaceous earth at 150-160° C. for 30-35 min, dispersing the diatomaceous earth in an oxalic acid solution, filtering, washing with water, and drying to obtain pretreated diatomaceous earth; (2) dispersing nano-silica in a sodium hydroxide solution, soaking for 1-2 hours, washing with water, and drying to obtain pretreated nano-silica; (3) Dispersing the diatomaceous earth pretreated in step (1) in water, adding the nano-silica, sodium rosin acid and xanthan gum pretreated in step (2), stirring for 2-3 hours, and drying to obtain modified diatomaceous earth.
[0019] By adopting the above technical scheme, diatomite is first calcined to remove impurities such as organic matter and carbonates in the diatomite, thereby improving the volcanic ash activity, thermal stability and adsorption of the diatomite. Then, it is mixed with oxalic acid to remove metal impurities in the diatomite, especially metal ions such as iron and manganese, thereby further improving the purity and whiteness of the diatomite and improving the adsorption performance of the diatomite.
[0020] Nano-silica has an extremely small particle size and can fill the tiny pores and capillary voids inside diatomaceous earth, thereby improving the density and compactness of diatomaceous earth. The surface of nano-silica is treated with sodium hydroxide solution to increase the specific surface area and adsorption of nano-silica, making it easy for nano-silica to be loaded on the surface and pores of diatomaceous earth, thereby subsequently improving the compressive strength, wear resistance, flexural strength and fracture toughness of the backfill material and enhancing the durability of the backfill material.
[0021] Pretreated diatomite, pretreated nano-silica, sodium rosinate and xanthan gum are mixed. Nano-silica can be loaded on the surface and pores of diatomite. Sodium rosinate can improve the dispersibility and fluidity of nano-silica, so that the dispersibility and fluidity are evenly loaded on the surface and pores of diatomite. Xanthan gum has a certain viscosity, so that nano-silica adheres to the surface and pores of diatomite, which increases the structural stability of the modified diatomite, so that the modified diatomite has better mechanical properties and durability, and is subsequently used in backfill with better comprehensive performance.
[0022] Preferably, the mass ratio of the diatomaceous earth, nano-silicon dioxide, sodium rosinate and xanthan gum is 1:0.5-0.7:0.06-0.08:0.1-0.2.
[0023] By adopting the above technical solution, the mass ratio of diatomite, nano-silicon dioxide, sodium rosin acid and xanthan gum is further limited within a certain range, the comprehensive performance of diatomite is improved, nano-silicon dioxide fills the tiny pores and capillary gaps inside the diatomite, reduces the pores and microcracks inside the material diatomite, and improves the crack resistance. Sodium rosin acid can improve the dispersibility and fluidity of nano-silicon dioxide, so that the dispersibility and fluidity are evenly loaded on the surface and pores of diatomite. The addition of xanthan gum can further reduce the shrinkage of diatomite during the drying process and reduce the risk of cracking. The combination of diatomite, nano-silicon dioxide, sodium rosin acid and xanthan gum further improves the mechanical properties and durability of the modified diatomite, and is subsequently used in backfill to improve the mechanical properties of the backfill.
[0024] Preferably, the preparation method of the modified chitosan comprises the following steps: dispersing chitosan in a sodium hydroxide solution, stirring for 20-25 minutes, then dispersing chitosan in an acetic acid solution, stirring evenly, adding carbon nanotubes, polypropylene fibers and lignin, stirring at a temperature of 90-95°C for 1-2 hours, and drying to obtain modified chitosan.
[0025] By adopting the above technical solution, chitosan and sodium hydroxide can form a colloid after mixing, and the chitosan solution can be gelled by utilizing the physical effects within and between chitosan molecules, thereby enhancing the strength and stability of the colloid. Carbon nanotubes have extremely high strength and toughness, and are loaded in the chitosan structure to improve the mechanical properties of chitosan such as tensile strength and toughness. Moreover, chitosan has good dispersion stability for carbon nanotubes under acidic conditions, which can effectively prevent the agglomeration of carbon nanotubes in the solution and improve its dispersibility in the mixed system.
[0026] Polypropylene fiber has high strength and toughness. After being compounded with chitosan and carbon nanotubes, it can enhance the mechanical properties of the system, such as tensile strength and compressive strength, making it stronger when subjected to external forces. Lignin can be embedded in the network structure formed by chitosan and polypropylene fibers, combined with carbon nanotubes, to improve the load stability of carbon nanotubes, improve the tensile strength, compressive strength and toughness of chitosan, and make chitosan have better viscosity and mechanical properties. It is subsequently applied to backfill, so that the components in the backfill are evenly bonded, and the mechanical properties of the backfill are improved, which can improve its tensile strength, compressive strength and toughness, making it less likely to be damaged when subjected to external forces.
[0027] Preferably, the mass ratio of chitosan, carbon nanotubes, polypropylene fibers and lignin is 1:0.2-0.4:0.3-0.5:0.05-0.07.
[0028] By adopting the above technical scheme, the mass ratio of chitosan, carbon nanotubes, polypropylene fibers and lignin is further limited within a certain range. Carbon nanotubes have extremely high strength and toughness and can be loaded in the chitosan structure to improve the mechanical properties of chitosan such as tensile strength and toughness. Polypropylene fibers and chitosan are composited to form a network structure to improve the mechanical properties and viscosity of chitosan. Lignin can be embedded in the network structure formed by chitosan and polypropylene fibers and combined with carbon nanotubes to improve the load stability of carbon nanotubes, so that the modified chitosan has better mechanical properties and viscosity. It is subsequently applied to backfill materials to ensure that the components in the backfill materials are evenly bonded, thereby improving the tensile strength, compressive strength and toughness of the backfill materials and preventing them from being easily damaged when subjected to external forces.
[0029] In the second aspect, the present application also provides a method for preparing backfill material for shallow wet and soft foundation of roads, comprising the following steps: grinding construction waste and modified diatomaceous earth to a particle size not greater than 80 mesh respectively, then dispersing them in water, adding cement, modified chitosan and sodium carbonate, stirring evenly, and obtaining backfill material for shallow wet and soft foundation of roads.
[0030] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing shallow wet soft foundation backfill for roads. The obtained shallow wet soft foundation backfill for roads has good mechanical properties.
[0031] Preferably, the stirring speed is 100-120 r / min and the stirring time is 60-75 min.
[0032] By adopting the above technical solution, the rotation speed and time of stirring are further limited, so that the mixture is mixed evenly, which helps to improve the comprehensive performance of the backfill material.
[0033] In summary, this application has the following beneficial effects: 1. In the present application, the construction waste soil is used as backfill material, which not only realizes the resource utilization of waste, but also has a good microstructure, which is helpful to mix with other components to form a dense mixture; the modified diatomaceous earth has a porous structure, high specific surface area and adsorption, and can adhere to the surface and pores of the construction waste soil, refine the pore structure of the backfill material, reduce the internal coarse pores, increase the fine pores, increase the porosity of the backfill material, and improve the antifreeze performance of the backfill material.
[0034] 2. The modified chitosan in the present application has good biocompatibility and reinforcing properties, and can be filled between construction waste, modified diatomaceous earth and cement, so that the various components in the backfill material are closely bonded, the density of the backfill material is improved, the compressive strength, tensile strength and toughness of the backfill material are enhanced, cracking is reduced, and the anti-cracking performance of the backfill material is improved.
[0035] 3. The fly ash in this application has certain viscosity and mechanical properties, and can be loaded on the surface and pores of construction waste to improve the mechanical properties of construction waste. The silane coupling agent can form chemical bonds between the fly ash and the construction waste, enhance the interface bonding between the fly ash and the construction waste, and improve the overall performance of the backfill material, including its mechanical properties and durability. DETAILED DESCRIPTION
[0036] The present application is further described in detail below with reference to the embodiments.
[0037] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0038] Preparation example of modified diatomite Preparation Example 1-1 The preparation method of modified diatomite comprises the following steps: (1) calcining 1.5 kg of diatomaceous earth at 155° C. for 35 min, dispersing the diatomaceous earth in 2 L of 20% by mass oxalic acid solution, filtering, washing with water, and drying to obtain pretreated diatomaceous earth; (2) dispersing the nano-silica in 1.9 L of a 12% sodium hydroxide solution, soaking for 2 h, washing with water, and drying to obtain pretreated nano-silica; (3) Disperse the diatomaceous earth pretreated in step (1) in 3 L of water, add the nano-silica, sodium rosin acid and xanthan gum pretreated in step (2), stir for 3 h, and dry to obtain modified diatomaceous earth.
[0039] The mass ratio of diatomaceous earth, nano-silicon dioxide, sodium rosinate and xanthan gum is 1:0.5:0.06:0.1.
[0040] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no nano-silicon dioxide is added.
[0041] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), sodium rosinate is not added.
[0042] Preparation Example 1-4 The difference from Preparation Example 1-1 is that in step (3), no xanthan gum is added.
[0043] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of diatomaceous earth, nano-silicon dioxide, sodium rosinate and xanthan gum is 1:0.7:0.08:0.2.
[0044] Preparation Example 1-6 The difference from Preparation Example 1-1 is that the mass ratio of diatomaceous earth, nano-silicon dioxide, sodium rosinate and xanthan gum is 1:0.1:0.2:0.03.
[0045] Preparation example of modified chitosan Preparation Example 2-1 The preparation method of modified chitosan comprises the following steps: dispersing 1.2 kg of chitosan in 1.5 L of 12% sodium hydroxide solution by mass, stirring for 25 min, then dispersing in 1.9 L of 10% acetic acid solution by mass, stirring evenly, adding carbon nanotubes, polypropylene fibers and lignin, stirring at a temperature of 95° C. for 2 h, and drying to obtain modified chitosan.
[0046] The mass ratio of chitosan, carbon nanotubes, polypropylene fibers and lignin is 1:0.2:0.3:0.07.
[0047] Preparation Example 2-2 The difference from Preparation Example 2-1 is that no carbon nanotubes are added.
[0048] Preparation Example 2-3 The difference from Preparation Example 2-1 is that no polypropylene fiber is added.
[0049] Preparation Example 2-4 The difference from Preparation Example 2-1 is that no lignin was added.
[0050] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of chitosan, carbon nanotubes, polypropylene fibers and lignin is 1:0.4:0.5:0.05.
[0051] Preparation Example 2-6 The difference from Preparation Example 2-1 is that the mass ratio of chitosan, carbon nanotubes, polypropylene fibers and lignin is 1:0.1:0.8:0.01. Example
[0052] Example 1 A backfill material for shallow soft foundation of a road, comprising the following raw materials by weight: 40 kg of construction waste, 10 kg of modified diatomaceous earth, 15 kg of cement, 7 kg of modified chitosan, 60 kg of water, and 9 kg of sodium carbonate; The pretreatment of construction waste soil comprises the following steps: crushing 60 kg of construction waste soil, dispersing it in 70 L of anhydrous ethanol, stirring it for 1-2 hours, drying it, heating it at 450° C. for 35 minutes, dispersing it in 75 L of water, adding fly ash and silane coupling agent KH-450, stirring it at a temperature of 85° C. for 2 hours, and drying it to obtain construction waste soil.
[0053] The mass ratio of construction waste, fly ash and silane coupling agent is 1:0.2:0.08.
[0054] Construction debris includes concrete blocks, bricks and stones generated when old buildings are demolished.
[0055] The preparation method of the shallow soft foundation backfill material of the road comprises the following steps: grinding construction waste soil and modified diatomaceous earth to a particle size of no more than 80 meshes respectively, dispersing them in water, adding cement, modified chitosan and sodium carbonate, stirring evenly, and obtaining the shallow soft foundation backfill material of the road.
[0056] The stirring speed is 120r / min and the stirring time is 75min.
[0057] The modified diatomaceous earth was prepared by using Preparation Example 1-1; and the modified chitosan was prepared by using Preparation Example 2-1.
[0058] Example 2 A backfill material for shallow soft foundation of a road, which differs from Example 1 in that it comprises the following raw materials by weight: 50 kg of construction waste, 15 kg of modified diatomaceous earth, 20 kg of cement, 10 kg of modified chitosan, 70 kg of water, and 5 kg of sodium carbonate.
[0059] Example 3 A backfill material for shallow wet soft foundation of a road, which differs from Example 1 in that fly ash is not added in the pretreatment of construction waste.
[0060] Example 4 A backfill material for shallow wet soft foundation of a road, which differs from Example 1 in that silane coupling agent KH-450 is not added in the pretreatment of construction waste.
[0061] Example 5 A backfill material for shallow wet soft foundation of a road, which differs from Example 1 in that the mass ratio of construction waste soil, fly ash and silane coupling agent KH-450 is 1:0.3:0.09.
[0062] Example 6 A backfill material for shallow wet soft foundation of a road, which differs from Example 1 in that the mass ratio of construction waste soil, fly ash and silane coupling agent KH-450 is 1:0.8:0.01.
[0063] Example 7 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified diatomaceous earth is prepared using Preparation Example 1-2.
[0064] Example 8 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified diatomaceous earth is prepared using Preparation Examples 1-3.
[0065] Example 9 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified diatomaceous earth is prepared using Preparation Examples 1-4.
[0066] Example 10 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified diatomaceous earth is prepared using Preparation Examples 1-5.
[0067] Embodiment 11 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified diatomaceous earth is prepared using Preparation Examples 1-6.
[0068] Example 12 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified chitosan is prepared using Preparation Example 2-2.
[0069] Example 13 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified chitosan is prepared using Preparation Example 2-3.
[0070] Embodiment 14 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified chitosan is prepared using Preparation Examples 2-4.
[0071] Embodiment 15 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified chitosan is prepared using Preparation Examples 2-5.
[0072] Example 16 A backfill material for shallow soft foundation of a road, which is different from Example 1 in that the modified chitosan is prepared using Preparation Examples 2-6.
[0073] Comparative Example Comparative Example 1 A backfill material for shallow soft foundation of a road, which differs from Example 1 in that modified diatomaceous earth is not added.
[0074] Comparative Example 2 A backfill material for shallow soft foundation of a road, which differs from Example 1 in that the modified diatomaceous earth is replaced by an equal amount of diatomaceous earth.
[0075] Comparative Example 3 A backfill material for shallow soft foundation of a road, which differs from Example 1 in that modified chitosan is not added.
[0076] Comparative Example 4 A backfill material for shallow wet soft foundation of a road, which differs from Example 1 in that the modified chitosan is replaced by an equal amount of chitosan.
[0077] Performance testing The performance of the shallow soft foundation backfill materials of the road prepared in Examples 1-16 and Comparative Examples 1-4 was tested. The compressive strength, tensile strength and other performance indicators were tested according to the "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" (GB / T50081-2002). The test results are shown in Table 1.
[0078] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, the backfill materials prepared in Examples 1-2 of the present application have good mechanical properties and mechanical strength. Among them, the compressive strength of Example 1 reaches 7.2 MPa at 1 day, 12.5 MPa at 7 days, and 18.9 MPa at 14 days. The tensile strength is 2.13 MPa, the slump is 220 mm at 0 h, 210 mm at 1 h, and 200 mm at 2 h. There are no cracks, indicating that the prepared backfill materials for shallow soft foundation of the road have good mechanical properties and mechanical strength. The various components cooperate with each other, which helps to reduce the microcracks of the backfill materials, improve the strength and durability of the backfill materials, and subsequently extend the service life of the building.
[0079] In Example 3, fly ash is not added in the pretreatment of construction waste soil. In Example 4, silane coupling agent is not added in the pretreatment of construction waste soil. In Examples 5-6, the mass ratio of construction waste soil, fly ash and silane coupling agent is changed. As can be seen from Table 1, compared with Example 1, the test results of compressive strength, tensile strength, slump and crack resistance of Examples 3-4 at 1 day, 7 days and 14 days are significantly worse than those of Examples 1-2 and Example 5, while the test results of compressive strength, tensile strength, slump and crack resistance of Example 6 at 1 day, 7 days and 14 days are significantly worse than those of Examples 1-2 and Example 5. The performance test is better than that of Examples 3-4, but worse than that of Examples 1 and 5, indicating that fly ash has certain viscosity and mechanical properties, can be loaded on the surface and pores of construction debris, and improve the mechanical properties of construction debris. The silane coupling agent can form a chemical bond between fly ash and construction debris, enhance the interface bonding between fly ash and construction debris, improve the overall performance of the backfill material, and also improve the crack resistance of the backfill material of the shallow wet soft foundation of the road, reduce the cracking phenomenon caused by temperature changes or humidity changes, and improve the durability of the backfill material.
[0080] In the preparation method of modified diatomite in Examples 7-9, nano silicon dioxide, sodium rosinate and xanthan gum are not added respectively. In Examples 10-11, the mass ratio of diatomite, nano silicon dioxide, sodium rosinate and xanthan gum is changed. As can be seen from Table 1, compared with Example 1, the test results of compressive strength, tensile strength, slump and crack resistance of Examples 7-9 at 1 day, 7 days and 14 days are significantly worse than those of Examples 1-2, and the test results of compressive strength, tensile strength, slump and crack resistance of Example 11 at 1 day, 7 days and 14 days are significantly worse than those of Examples 1-2, but significantly better than those of Examples 1-2. 7-9, indicating that nano-silica fills the tiny pores and capillary voids inside diatomite, reduces the pores and microcracks inside the diatomite material, and improves the crack resistance. Sodium rosin acid can improve the dispersibility and fluidity of nano-silica, so that the dispersibility and fluidity are evenly loaded on the surface and pores of diatomite. The addition of xanthan gum can further reduce the shrinkage of diatomite during the drying process and reduce the risk of cracking. The combination of diatomite, nano-silica, sodium rosin acid and xanthan gum can further improve the mechanical properties and durability of the modified diatomite, and it can be subsequently used in backfill to improve the mechanical properties of the backfill.
[0081] In the preparation method of modified chitosan in Examples 12-14, carbon nanotubes, polypropylene fibers, and lignin are not added respectively. In Examples 15-16, the mass ratio of chitosan, carbon nanotubes, polypropylene fibers, and lignin is changed. As can be seen from Table 1, compared with Example 1, the test results of compressive strength, tensile strength, slump, and crack resistance of Examples 12-14 at 1 day, 7 days, and 14 days are significantly worse than those of Examples 1-2, and the test results of compressive strength, tensile strength, slump, and crack resistance of Example 16 at 1 day, 7 days, and 14 days are significantly worse than those of Examples 1-2, but significantly better than those of Examples 12-14. , indicating that carbon nanotubes have extremely high strength and toughness, can be loaded in the chitosan structure, and improve the mechanical properties of chitosan such as tensile strength and toughness. Polypropylene fiber and chitosan are composited to form a network structure, which improves the mechanical properties and viscosity of chitosan. Lignin can be embedded in the network structure formed by chitosan and polypropylene fiber, and combined with carbon nanotubes, which improves the load stability of carbon nanotubes, making the modified chitosan have better mechanical properties and viscosity. It is subsequently applied to backfill, so that the components in the backfill are evenly bonded, and the tensile strength, compressive strength and toughness of the backfill are improved, making it not easily damaged when subjected to external forces.
[0082] In Comparative Examples 1 and 3, modified diatomite and modified chitosan are not added, respectively. As can be seen from Table 1, compared with Example 1, the test results of compressive strength, tensile strength, slump and crack resistance of Comparative Examples 1 and 3 at 1 day, 7 days and 14 days are significantly worse than those of Examples 1-2, indicating that modified diatomite has good volcanic ash properties and can also react with cement hydration products to form a denser structure, thereby improving the compressive strength of the backfill material; modified chitosan has good biocompatibility and reinforcing properties, and can be filled between construction waste, modified diatomite and cement, so that various components in the backfill material are closely bonded, the density of the backfill material is improved, the compressive strength, tensile strength and toughness of the backfill material are enhanced, cracking is reduced, and the crack resistance of the backfill material is improved.
[0083] In Comparative Examples 2 and 4, the modified diatomaceous earth is replaced by an equal amount of diatomaceous earth, and the modified chitosan is replaced by an equal amount of chitosan. It can be seen from Table 1 that, compared with Example 1, the test results of the compressive strength, tensile strength, slump and crack resistance of Comparative Examples 2 and 4 at 1 day, 7 days and 14 days are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified diatomaceous earth and modified chitosan of the present application have good mechanical properties, thereby improving the mechanical properties of the backfill material and maintaining the structural strength and stability of the backfill material.
[0084] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A backfill material for shallow soft foundation of a road, characterized in that: The raw materials include, by weight: 40-50 parts of construction waste soil, 10-15 parts of modified diatomaceous earth, 15-20 parts of cement, 7-10 parts of modified chitosan, 60-70 parts of water and 5-9 parts of sodium carbonate.
2. The shallow soft foundation backfill material of a road according to claim 1, characterized in that: The pretreatment of the construction waste soil comprises the following steps: crushing the construction waste soil, dispersing it in anhydrous ethanol, stirring, drying, heating it at 400-450° C. for 30-35 minutes, dispersing it in water, adding fly ash and silane coupling agent, stirring it at 80-85° C. for 1-2 hours, and drying it to obtain the construction waste soil.
3. The shallow soft foundation backfill material of a road according to claim 2, characterized in that: The mass ratio of the construction waste soil, fly ash and silane coupling agent is 1:0.2-0.3:0.08-0.
09.
4. The shallow soft foundation backfill material of a road according to claim 2, characterized in that: The construction debris includes concrete blocks, bricks and stones generated when old buildings are demolished.
5. The shallow soft foundation backfill material of a road according to claim 1, characterized in that: The preparation method of the modified diatomite comprises the following steps: (1) calcining diatomaceous earth at 150-160° C. for 30-35 min, dispersing the diatomaceous earth in an oxalic acid solution, filtering, washing with water, and drying to obtain pretreated diatomaceous earth; (2) dispersing nano-silica in a sodium hydroxide solution, soaking for 1-2 hours, washing with water, and drying to obtain pretreated nano-silica; (3) Disperse the diatomite pretreated in step (1) in water, add the nano-silica, sodium rosin acid and xanthan gum pretreated in step (2), stir for 2-3 hours, and dry to obtain modified diatomite.
6. The shallow soft foundation backfill material of a road according to claim 5, characterized in that: The mass ratio of the diatomaceous earth, nano silicon dioxide, sodium rosinate and xanthan gum is 1:0.5-0.7:0.06-0.08:0.1-0.
2.
7. The shallow soft foundation backfill material of a road according to claim 1, characterized in that: The preparation method of the modified chitosan comprises the following steps: dispersing chitosan in a sodium hydroxide solution, stirring for 20-25 minutes, then dispersing chitosan in an acetic acid solution, stirring evenly, adding carbon nanotubes, polypropylene fibers and lignin, stirring at a temperature of 90-95° C. for 1-2 hours, and drying to obtain the modified chitosan.
8. The shallow soft foundation backfill material of a road according to claim 7, characterized in that: The mass ratio of the chitosan, carbon nanotubes, polypropylene fibers and lignin is 1:0.2-0.4:0.3-0.5:0.05-0.
07.
9. The method for preparing backfill material for shallow soft foundation of a road according to claim 1, characterized in that: The method comprises the following steps: grinding construction waste soil and modified diatomaceous earth to a particle size of no more than 80 meshes respectively, dispersing them in water, adding cement, modified chitosan and sodium carbonate, stirring evenly, and obtaining shallow wet soft foundation backfill material for roads.
10. The method for preparing backfill material for shallow soft foundation of a road according to claim 9, characterized in that: The stirring speed is 100-120 r / min, and the stirring time is 60-75 min.
Citation Information
Cited By
Hard rock tunneling muck recycling improvement process construction method
CN120172687A
Hard rock tunneling slag resource utilization improvement process
CN120172687B